2010
DOI: 10.1186/1471-2407-10-159
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative effect of extremely low frequency electromagnetic field on preneoplastic lesions formation in the rat liver

Abstract: BackgroundRecently, extremely low frequency electromagnetic fields (ELF-EMF) have been studied with great interest due to their possible effects on human health. In this study, we evaluated the effect of 4.5 mT - 120 Hz ELF-EMF on the development of preneoplastic lesions in experimental hepatocarcinogenesis.MethodsMale Fischer-344 rats were subjected to the modified resistant hepatocyte model and were exposed to 4.5 mT - 120 Hz ELF-EMF. The effects of the ELF-EMF on hepatocarcinogenesis, apoptosis, proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
(45 reference statements)
1
34
1
Order By: Relevance
“…5). Other researches also confirmed that EL-EMF cannot promote caspase activation and cannot trigger the apoptosis pathway (Akdag et al 2010) (Jiménez-García et al 2010). Pirozzoli et al (2003) finding confirmed our results.…”
Section: Dapi Staining Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…5). Other researches also confirmed that EL-EMF cannot promote caspase activation and cannot trigger the apoptosis pathway (Akdag et al 2010) (Jiménez-García et al 2010). Pirozzoli et al (2003) finding confirmed our results.…”
Section: Dapi Staining Resultssupporting
confidence: 88%
“…These effects may be enhanced when EL-EMFs and cisplatin are applied in combination and in this way also intensify the effects of cisplatin to cell death induction. It was reported that EL-EMF was associated with a reduction of cell proliferation and this suggests that ELF-EMF protects hepatocytes from the increased proliferation induced by treatment with carcinogene (Jiménez-García et al 2010). This effect of EL-EMF in combination with cisplatin may affect viability rate.…”
Section: Possible Mechanismmentioning
confidence: 95%
“…The results showed a decrease of more than 50% of the number and the area of γ-glutamyl transpeptidase-positive preneoplastic lesions, glutathione S-transferase placental expression, as well as a significant decrease of proliferating cell nuclear antigen, Ki-67, and cyclin D1 expression. These findings showed inhibition of preneoplastic lesions, through antiproliferative activity of ELF-EMF (Jimenez-Garcia et al, 2010).…”
Section: In Vivo Studiesmentioning
confidence: 83%
“…While several studies suggested that EMF exposure induces immune cell activation and DNA damage (10,11), the findings of other studies indicated that the effects of EMF inhibit preneoplastic lesions, resulting in the reduction of cell proliferation (3). A number of studies focused on the potential effects of EMF at cancer treatment (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Findings of previous studies have demonstrated variations in cell proliferation and apoptosis subsequent to exposure to ELF fields (2,3), while such changes have not been identified in other studies (4). Thus, a careful examination of the literature in this field suggests that more studies examining the role of ELF fields in cancer should be conducted.…”
Section: Introductionmentioning
confidence: 98%